2019
DOI: 10.3390/nu11102352
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Saccharomyces boulardii Increases the Maximal Oxygen Consumption and Maximal Aerobic Speed Attained by Rats Subjected to an Incremental-Speed Exercise

Abstract: Benefits to the host metabolism resulting from Saccharomyces boulardii (Sb) supplementation have been described; however, no study has investigated the effects of this supplementation on aerobic metabolism and performance during physical exercise. Thus, in the present study, we addressed the effects of Sb supplementation on the rate of oxygen consumption (VO2), mechanical efficiency (external work divided by VO2), and aerobic performance of rats subjected to fatiguing, incremental-speed exercise. Twenty-six ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…The previously described results of Scheiman et al [60] on Veillonella effects on athletic results can suggest a possible use of these strains as a supplement to improve performance. In a similar direction, Soares et al [163] recently highlighted the benefits to the host metabolism resulting from Saccaharomyces boulardii (Sb) supplementation. In this study, the authors evaluated the effect of Sb supplementation on the rate of oxygen consumption (VO 2 ), mechanical efficiency, and aerobic performance of Wistar rats subjected to fatiguing, incremental-speed exercise, and found that supplemental Sb does not affect resting aerobic metabolism, but significantly increases VO 2 max and aerobic performance.…”
Section: Probioticsmentioning
confidence: 98%
“…The previously described results of Scheiman et al [60] on Veillonella effects on athletic results can suggest a possible use of these strains as a supplement to improve performance. In a similar direction, Soares et al [163] recently highlighted the benefits to the host metabolism resulting from Saccaharomyces boulardii (Sb) supplementation. In this study, the authors evaluated the effect of Sb supplementation on the rate of oxygen consumption (VO 2 ), mechanical efficiency, and aerobic performance of Wistar rats subjected to fatiguing, incremental-speed exercise, and found that supplemental Sb does not affect resting aerobic metabolism, but significantly increases VO 2 max and aerobic performance.…”
Section: Probioticsmentioning
confidence: 98%
“…Common probiotic bacteria used were strains of Lactobacillus or Bifidobacterium (133,134,(136)(137)(138)(139)147). Additional strains tested included those belonging to species Bacillus subtillis (140) or Bacillus coagulans (135), Veillonella atypica (141), or even yeast Saccharomyces boulardii (142). The majority of studies investigated the effect of probiotic supplementation on aerobic exercise performance measures such as run time-to-fatigue, VO 2max , max speed attained, 10yard sprint, or 400-meter swim time (132-134, 136, 138, 139, 141, 142).…”
Section: The Effect Of Probiotic Supplementation On Athlete Health Anmentioning
confidence: 99%
“…In addition to performance variables, many of these studies investigated effects on body composition and inflammation. Again, results were mixed, with some studies reporting significant effects of supplementation on outcomes such as fat mass and muscle mass (132,133) or inflammatory markers (133,137,139,141,147), though results were often mixed with some biochemical markers showing no significant effect of probiotic treatment and some studies showing no significant effects at all on these outcomes (134,142). However, as none of these variables were analyzed, further research is necessary to determine the mechanism of the effects as well as whether the same effects are seen in humans.…”
Section: The Effect Of Probiotic Supplementation On Athlete Health Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, multiple probiotics were added to increase maximum oxygen uptake, aerobic capacity, training load, and increase physical exertion time, only a few studies point to single-strain probiotic supplementation has produced a significant aerobic performance benefit [27]. Previous studies have shown that supplementation of Saccharomyces boulardii in rats undergoing accelerated exercise increased maximum oxygen consumption by 12.7%, maximum aerobic speed by 12.4%, and running time to fatigue by 21.6%, compared to with sedentary the control group [40]. In our previous study, the Bifidobacterium longum (OLP-01) isolated from a weightlifting gold medalist found that, not only help in fatigue indicators, but also significantly increased 1.77-3.37-fold exercise to exhaustive time by 1X, 2X and 5X dose OLP-01 supplementation for four weeks, in addition, it also has a significant increase in forelimb grip, although there is no significant difference in muscle mass [16].…”
Section: Discussionmentioning
confidence: 99%